Cold War as Cooperation - Kanet, Roger E. author. aut Link
XV, 439 p.
Keywords: A study of superpower co-operation since World War II, this book examines the regulation of USA/USSR rivalry, and outlines the power of regional states to constrain and manipulate them for their own interests.